Culture and Nature in The Jaguar Smile (International Journal of Food and Nutritional Sciences, 2022)
The Jaguar Smile: A Nicaraguan Journey written by Salman Rushdie is a non-fiction book that gives the reader insight into the internal turmoil taking place in the nation of Nicaragua. Salman Rushdie is a British-Indian novelist who gained his fame for his novels about the post-colonial relationship between cultures of the East and West. Rushdie became interested in Nicaraguan affairs when the Reagan administration started its ‘war’ against Nicaragua. Rushdie made his trip to Nicaragua in July of 1986. He came to know a wide range of people from the President to the everyday citizens. His perceptions were always heightened by his sensitivity and his unique flair for language. In this book Rushdie brings before us the true Nicaragua where nothing is simple, everything is contested, and life-or-death struggles are an everyday occurrence. This environment has become the culture of this place. Rushdie talks about how in order to understand the living, it is necessary to first understand the dead. This is a powerful statement because it gives you an idea of how many lives were lost during the Nicaraguan Revolution. He immediately follows this statement by describing in great detail the presence of the toppled statue of the ex-dictator Anastasio Somoza Debayle. This contributes to the image that Nicaragua is a nation in shambles after the constant turmoil of the past. Rushdie spends a lot of his time in Nicaragua with members of the Frente Sandinista de Liberacion Nacional, otherwise known as the FSLN. The FSLN was the group that led the campaign in the revolution against the Somoza dictatorship.